SAND SOIL CLOGGING PHENOMENON IN VERTICAL FLOW OF GROUNDWATER RECHARGE WELL (LABORATORY SIMULATION) - MARETTA (NIM : 25314001), ALDILA
Aquifer recharge, which uses urban stormwater, is an effective technique to control negative effects of groundwater exploitation. Meanwhile, there is soil clogging problem which is a restricting factor of groundwater recharge application. Clogging is commonly caused by suspended solid present in water study physical clogging phenomenon in soil because of suspended solid present which happens in groundwater recharge process in recharge well. Laboratory simulation is conducted using soil column with dimension are are 4,5 cm inside diamater and 20 cm in height and using sand soil as porous medium. The water used in this research is made by mixing the clay soil with water and the concentrations of TSS in water are 150 mg/l (simulation 1), 250 mg/l (simulation 2), and 500 mg/l (simulation 3 and 4). The results show that there are effects of TSS concentration to the amount of retained suspended solid, to the declining of hydraulic conductivity, and to the clogging time. The clogging mechanism that happen in two simulations is surface clogging. Laboratory results are used to determine empirical constant of power equation that it used to predict soil hydraulic conductivity value of every simulation. Power equation from simulation 3 and 4 result with empirical flow-through constants are 0.0007; dan 0.0003 and empirical exponential constants are -0.148; and -0.116 that can predict soil hyrdaulic conductivity value of simulation 3 and 4 well.